THE IMPROVEMENT OF COVID-19 HEALTH PROTOCOL IN TPQ AL AMIN NGIJO WETAN, TASIKMADU, KARANGANYAR - Arini, Liss Dyah Dewi; Firdaus, Erma Nurhayati; Suwanto (Lux Mensana: Journal of Scientific Health, 2022)
Washing hands with soap is one way to prevent various infectious diseases; one of them is Covid-19. Human fingers can become an entrance for viruses that cause Covid-19. Therefore, washing hand is the one effective and efficient prevention to avoid Covid-19 infection. This community service was conducted at TPQ Al Amin Ngijo Wetan, Tasikmadu, Karanganyar with 60 students with the aim of knowing the description of clean and healthy living behavior in TPQ. From the observation results, it found that many of students did not fully understand about health problems and did not implementing the disciplinary behavior of washing hands with soap. This can be seen from students' hands that look dirty and they used it directly to eat the food that they buy without washing their hands, also they used their hand for touching their face without washing it after playing around TPQ. Therefore, this community service is conducted to provide students understanding in improving the washing hands with soap behavior. The method used in this community service are counseling, video screening, training, monitoring and evaluation. Researchers hoped that this research is able to have a positive impact in increasing awareness towards cleanliness and can actually implement by TPQ students.